Student’s Responses on Learning in the Early COVID-19 Pandemic - Wargadinata, Wildana; Maimunah, Iffat; Dewi, Eva; Rofiq, Zainur (Universitas Islam Negeri Raden Intan Lampung, 2020)
The coronavirus disease (COVID-19) pandemic forced many universities to apply online learning. The purpose of this study was to break down the online learning process in the early pandemic as well as effective and optimal online learning. The design of this research is descriptive qualitative research. The data were collected through observation, questionnaires, interviews, and documentation. Interestingly, this study found online learning using the WhatsApp Group to be the most effective in the early COVID-19 pandemic. WhatsApp is easy, simple, and does not require a large data quota package. Through WhatsApp accounts, learning took place optimally because students and lecturers could communicate and share PowerPoint files, Microsoft Word files, JPGs, Voice Notes, Videos, and other learning resource links. The study recommends that other researchers uncover the solution to obstacles experienced by students in online learning and the development of other media to implement effective online lectures.